2022
DOI: 10.48550/arxiv.2203.13112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

minicons: Enabling Flexible Behavioral and Representational Analyses of Transformer Language Models

Abstract: We present minicons, an open source library that provides a standard API for researchers interested in conducting behavioral and representational analyses of transformer-based language models (LMs). Specifically, minicons enables researchers to apply analysis methods at two levels: (1) at the prediction levelby providing functions to efficiently extract word/sentence level probabilities; and (2) at the representational level-by also facilitating efficient extraction of word/phrase level vectors from one or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Therefore, in the following we primarily focus on the surprisal values obtained from GPT-3.5. For calculating surprisal with GPT-2, we utilized the implementation by Misra ( 2022 ). The detailed GPT-2 results, along with a corresponding plot, can be accessed on GitHub ( https://www.github.com/tjuzek/om-uid ).…”
Section: More Quantitative Datamentioning
confidence: 99%
“…Therefore, in the following we primarily focus on the surprisal values obtained from GPT-3.5. For calculating surprisal with GPT-2, we utilized the implementation by Misra ( 2022 ). The detailed GPT-2 results, along with a corresponding plot, can be accessed on GitHub ( https://www.github.com/tjuzek/om-uid ).…”
Section: More Quantitative Datamentioning
confidence: 99%
“…Each image is presented on a white background (see Figure 1). For LLaVA, we compare the log-probabilities of the model using the basic or subordinate label as a continuation to the prompt using the minicons library (Misra, 2022). We code a response as basic if P(basic|prompt, image) > P(subordinate|prompt, image) and subordinate otherwise.…”
Section: ✓ ✓mentioning
confidence: 99%
“…Surprisal for each non-initial word in the sentences was estimated using probabilities generated by the open source transformer language model GPT-2 (Radford et al 2019), as shown for the regions surrounding the verb in Figure 2. These surprisals were calculated in Python using the minicons package (Misra 2022), which provides convenience wrappers for the Hugging Face transformers library (Wolf et al 2020). 3.1.4.…”
Section: Tasks For Investigating the Role Of Predictionmentioning
confidence: 99%